DYNAMICS OF MILLET STRAW CULTIVATED AT DIFFERENT SOWING DATES IN THE OFF-SEASON - BOLDRIN, MARUSSA CÁSSIA FAVARO; DE ASSIS, RENATO LARA; COSTA, KÁTIA APARECIDA DE PINHO; SIMON, GUSTAVO ANDRÉ; PEREIRA BRAZ, ANTONIO JOAQUIM BRAGA; DA SILVA, ALESSANDRO GUERRA; TORRES, JOSÉ LUIZ RODRIGUES; MORAES TAVARES, ROSE LUIZA (REVISTA BRASILEIRA DE MILHO E SORGO, 2022)
The millet straw dynamics at different sowing dates in the off-season were evaluated in an experiment conducted in Rio Verde-GO. The experimental design used was randomized blocks arranged in a split-plot scheme, with four replications and four sowing dates. Five millet genotypes, two cultivars (ADR300 and ADR500) for biomass production, a dual-purpose hybrid (ADR8010) for grain and biomass production, and two hybrids (ADR9010 and ADR 9020) for grain production were used. Biomass production was performed at 0, 60, 94, 140, and 178 days after grain harvest. The millet cultivars and hybrids showed similar dry biomass production at different sowing dates, with an average production of 8,917 kg ha-1. The ADR300 and ADR500 cultivars and the ADR8010 hybrid showed similar dry biomass decomposition rates at all sowing dates. The hybrids ADR9010 and ADR9020 showed lower rates of straw decomposition in the fourth sowing date than the other genotypes. The hybrids ADR9010 and ADR9020, specific for grain production, have the potential for biomass production similar to the cultivars, regardless of the sowing dates.